Introduction to nuclear science - Bryan, Jeff C (Boca Raton, FL : CRC Press/ Taylor & Francis Group, 2013)
'This introductory textbook covers general aspects of nuclear chemistry and physics. It discusses how nuclear science impacts our daily lives through medicine, electrical power generation, food safety, waste, and weapons. This second edition features four new chapters that address nuclear reactors, dosimetry, radiochemistry, and nuclear forensics. It also expands coverage of nuclear medicine and radiation therapy. With additional end-of-chapter problems, the text provides critical information for students earning nuclear-related degrees in the coming years, as well as providing an accessible reference for anyone with some post-secondary education and an interest in nuclear issues'--
Machine generated contents note: ch. 1 Introduction -- 1.1. Radiation -- 1.2. Atomic Structure -- 1.3. Nuclear Transformations -- 1.4. Nuclear Stability -- 1.5. Ionizing Radiation -- 1.6.A Biological Threat -- 1.7. Natural and Anthropogenic Radiation -- 1.8. The Chart of the Nuclides -- Questions -- ch. 2 Mathematics of Radioactive Decay -- 2.1. Atomic Masses and Average Atomic Masses -- 2.2. Nature of Decay -- 2.3. Specific Activity -- 2.4. Dating -- 2.5. Branched Decay -- 2.6. Equilibria -- 2.6.1. Secular Equilibrium -- 2.6.2. Transient Equilibrium -- 2.6.3. No Equilibrium -- 2.7. Statistics -- Questions -- ch. 3 Energy and the Nucleus -- 3.1. Binding Energy -- 3.2. Total Energy of Decay -- 3.3. Decay Diagrams -- Questions -- ch. 4 Applications of Nuclear Science I: Power and Weapons -- 4.1. Nuclear Power -- 4.1.1. Nuclear Fission -- 4.1.2. Nuclear Reactors -- 4.1.3. Nuclear Fuel -- 4.1.4. Reactor Safety -- 4.1.5. Nuclear Waste -- 4.1.6. Cost of Nuclear Power -- 4.1.7. Proliferation of Nuclear Weapons -- 4.2. Nuclear Weapons -- 4.2.1. Fission Bombs -- 4.2.2. Fusion Bombs -- 4.2.3. Other Bombs -- 4.3. Nuclear Forensics -- Questions -- ch. 5 Radioactive Decay: The Gory Details -- 5.1. Alpha Decay -- 5.2. Beta Decay -- 5.3. Positron Decay -- 5.4. Electron Capture -- 5.5. Multiple Decay Modes -- 5.6. Valley of Beta Stability -- 5.7. Isomeric Transitions -- 5.8. Other Decay Modes -- 5.8.1. Spontaneous Fission -- 5.8.2. Cluster Decay -- 5.8.3. Proton/Neutron Emission -- 5.8.4. Delayed Particle Emission -- 5.8.5. Double Beta Decay -- Questions -- ch. 6 Interactions of Ionizing Radiation with Matter -- 6.1. Ionizing Radiation -- 6.2. Charged Particles -- 6.3. Photons -- 6.3.1.Compton Scattering -- 6.3.2. Photoelectric Effect -- 6.3.3. Pair Production -- 6.4. Attenuation of Gamma and X-Radiation -- Questions -- ch. 7 Detection of Ionizing Radiation -- 7.1. Gas-Filled Detectors -- 7.1.1. Ionization Chambers -- 7.1.2. Proportional Counters -- 7.1.3. Geiger-Muller Tubes -- 7.2. Scintillation Detectors -- 7.2.1. Photomultiplier Tubes -- 7.2.2. Inorganic Scintillators -- 7.2.3.Organic Scintillators -- 7.3. Other Detectors -- 7.3.1. Semiconductor Detectors -- 7.3.2. Thermoluminescent Dosimeters -- 7.4. Gamma Spectroscopy -- Questions -- ch. 8 Applications of Nuclear Science II: Medicine and Food -- 8.1. Radiology -- 8.2. Radiation Therapy -- 8.3. Food Irradiation -- 8.4. Nuclear Medicine -- 8.4.1. Radionuclide Production -- 8.4.2. Radiopharmaceuticals -- 8.4.3. Gamma Cameras -- Questions -- ch. 9 Nuclear Reactions -- 9.1. Energetics -- 9.2. Cross Section -- 9.3. Yield -- 9.4. Accelerators -- 9.5. Cosmogenic Nuclides -- Questions -- ch. 10 Fission and Fusion -- 10.1. Spontaneous Fission -- 10.2. Neutron-Induced Fission -- 10.3. Fusion -- 10.4. Stellar Nucleosynthesis -- 10.5. Synthesis of Unknown Elements -- Questions -- ch. 11 Applications of Nuclear Science III: More about Nuclear Reactors -- 11.1. Reactions in Reactors -- 11.2. Other Reactor Types -- 11.2.1. Pressurized Heavy Water Reactors -- 11.2.2. Gas-Cooled Reactors -- 11.2.3. Light Water Graphite Reactors -- 11.2.4. Small Modular Reactors -- 11.2.5. Thorium in Reactors -- 11.2.6. Generation IV Reactors -- 11.3. Reactor Safety Systems -- 11.4. Nuclear Power Plant Accidents -- 11.4.1. Three Mile Island -- 11.4.2. Chernobyl -- 11.4.3. Fukushima -- 11.5. Fusion Reactors -- Questions -- ch. 12 Radiation Protection -- 12.1. Terms -- 12.2. Regulations and Recommendations -- 12.3. Risk -- Questions -- ch. 13 X-Ray Production -- 13.1. Conventional X-Ray Beams -- 13.2. High-Energy X-Ray Beams -- Questions -- ch. 14 Dosimetry of Radiation Fields -- 14.1. Percent Depth Dose -- 14.2. Tissue-Air Ratio -- 14.3. Tissue Maximum Ratio -- 14.4. Isodose Curves -- 14.5. Moving Fields -- 14.6. Proton and Electron Beam Dosimetry -- Questions.
Includes bibliographical references (pages 391-392) and index.
Keywords: Nuclear physics; Nuclear chemistry